“I Feel Like Two In One”: Complex Belongings Among Namibian Czechs - Kateřina Mildnerová (Modern Africa, 2018)
This paper, based on the analysis of archive documents, biographical interviews and participant observation, focuses on the social and narrative construction of collective cultural identity of so-called Namibian Czechs living in Namibia. These represent a group of originally fifty-six Namibian child war refugees who received asylum and were educated in Czechoslovakia between 1985 and 1991. In order to understand their complex identity special attention has been paid to the dual education of the children in Czechoslovakia, to the role of the Czech language and the symbolical narratives in the construction of their collective cultural identity and to diverse discursive and social practices through which they shape, maintain, and reproduce their Czechness – both situationally in social interactions and narratively in a form of communicative memory.